Evaluation of a Solid Dispersion of Curcumin With Polyvinylpyrrolidone and Boric Acid Against Salmonella Enteritidis Infection and Intestinal Permeability in Broiler Chickens: A Pilot Study - Hernandez-Patlan, Daniel; Solis-Cruz, Bruno; Pontin, Karine Patrin; Latorre, Juan D.; Baxter, Mikayla F. A.; Hernandez-Velasco, Xochitl; Merino-Guzman, Ruben; Méndez-Albores, Abraham; Hargis, Billy M.; Lopez-Arellano, Raquel; Tellez, Guillermo (Frontiers in Microbiology, 2018)
In the present study, in vitro assays were conducted to evaluate the solubility of curcumin alone (CUR) or with polyvinylpyrrolidone (PVP) at different pH, as well as its permeability in Caco-2 cells. Results confirmed that the solid dispersion of CUR with PVP (CUR/PVP) at a 1:9 ratio, significantly increased (P < 0.05) solubility and permeability compared to CUR alone. Then, the antimicrobial activity of CUR/PVP, boric acid (BA) and a combination of 0.5 % CUR/PVP and 0.5 % BA (CUR/PVP-BA) against Salmonella Enteritidis (SE) was determined using an in vitro digestion model that simulates crop, proventriculus, and intestine. The results revealed that in the proventriculus and intestinal compartments significant reductions of SE were observed in all the experimental treatments, but 1 % BA eliminated SE in the intestinal compartment and CUR/PVP-BA showed a synergistic effect on antimicrobial activity against SE. To complement these findings, 2 independent in vivo trials were conducted to determine the effect of 0.1 % CUR/PVP; 0.1 % BA; or the combination of 0.05 % CUR/PVP (1:9 ratio) and 0.05 % BA (CUR/PVP-BA) on the antimicrobial activity against SE, intestinal permeability and inflammatory responses in broiler chickens. BA at 0.1 % had no significant in vivo effects against SE. However, the combination of 0.05% BA and 0.05% CUR/PVP and 0.05 % BA was sufficient to reduce crop and intestinal SE colonization in broiler chickens in two independent trials, confirming the synergic effect between them. A similar antimicrobial impact against SE intestinal colonization was observed in chickens treated with 0.1% CUR/PVP at a 1:9 ratio, which could be due to the increase in solubility of CUR by PVP. Furthermore, 0.1% CUR/PVP reduced the intestinal permeability of FITC-d and total intestinal IgA, as well as increase the activity of SOD when compared to control, while, CUR/PVP-BA only decreased SOD activity. Further studies to confirm and expand the in vivo results obtained in this pilot study, adding intestinal microbial commensal groups and more inflammatory biomarkers to get a complete description of the effects of BA and CUR deserves further investigation.